Harga Saham Perusahaan Perbankan: Inflasi, Kurs Valuta Asing, Dan Suku Bunga - Tasum Tasum (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2026)
This study aims to make a new contribution by examining in greater detail the effects of inflation, foreign exchange rates, and interest rates on stock prices, as well as identifying factors that can clarify these relationships within the context of the banking sector. The research design employed in this study is quantitative. The population used in this study consists of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period, comprising 55 companies. The analytical methods include descriptive statistics, testing of classical assumptions (normality, multicollinearity, autocorrelation, and heteroscedasticity), and multiple linear regression analyzed using SPSS version 27. The findings indicate that inflation and foreign exchange rates do not affect stock prices, whereas interest rates have a positive and significant effect on stock prices. The implications of this study suggest that banking companies should optimize and increase dividend payouts as a means to boost corporate profits. Such an increase in profits can attract investor interest in investing, which ultimately has the potential to increase the company’s stock prices.